Development Science E-Module Based PBL-Integrated STEM on Energy Material - Novia Puji Rahayu; Arif Widiyatmoko; Mintarsih Arbarini (Jurnal Penelitian Pendidikan IPA, 2024)
This research is to develop E-module of STEM-PBL mater energy based science. The method used in development research was adapted from the RnD method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data collection technique was in the form of a validated questionnaire for language experts, materials, media, and teachers responses.  E-module based Problem Based Learning contains five stages, namely; 1) orientation of students towards problems; 2) organizing students to learn; 3) guiding independent and group investigations; 4) develop and present the work; 5) analyze and evaluate the problem-solving process. In addition, the STEM in this e-module contains aspects of science, technology, engineering, and mathematics. The results of validation were, a percentage of 96.67% for language validation, a percentage of 95.00% for material validation, and a percentage of 96.00% for media validation, both of which were classified as very valid. Based on these results, it can be concluded that E-module based on STEM-PBL is feasible to be used in learning energy Materials.